Aspects of Tilapia Culture in Punjab, Pakistan (Proceedings International Conference on Fisheries and Aquaculture, 2018)
Tilapia culture is growing gradually in the province of Punjab, Pakistan. The mono sex culture of tilapia, Oreochromis niloticus is practiced on semi-intensive fish farming system. Both locally produced and imported mono sex tilapia fry is stocked in earthen ponds (stocking density 6250-10000 fry/ha). The fish is fed on high quality floating tilapia feed (30% protein). The fish is reared from April onwards and harvested in winter. The fish yield varies from 4400-7000kg/ha. This yield variation may be due to fish farm management and input administrated by the farmers. The tilapia has high local demand. The price of fresh iced fish depends on size of the fish. This year fish (600-700g) fetched good price (US$ 2.0/kg).  However, last year the price of fish was almost half than this year price. The polyculture of mono sex tilapia with major carp; Labeo rohita is also practiced by some fish farmers. The yield of these two species in polyculture is very high (average weight 900g and 3100g for O. niloticus and L. rohita respectively). Tilapia culture is growing fast in Southern and Central Punjab. Yet, fish farmers have raised the issues of high priced fish feed, low fry survival, fish health issues, fish processing and marketing. The aspects of tilapia culture in the province of Punjab, Pakistan are discussed.
Keywords: Tilapia; mono sex; poly culture; semi intensive